SURFACE CHEMISTRY OF DISORDERED MACKINAWITE (FES) - Wolthers M.; van Der Weijden C.H.; Charlet L.; van Der Linde P.R.; Rickard D. (My University, 2005)
Disordered mackinawite, FeS, is the first formed iron sulfide in ambient sulfidic environments and has a highly reactive surface. In this study, the solubility and surface chemistry of FeS is described. Its solubility in the neutral pH range can be described by Ksapp = {Fe2+ · {H2S(aq)} · {H+}-2 = 10+4.87±0.27. Acid-base titrations show that the point of zero charge (PZC) of disordered mackinawite lies at pH ~7.5. The hydrated disordered mackinawite surface can be best described by strongly acidic mono-coordinated and weakly acidic tricoordinated sulfurs. The mono-coordinated sulfur site determines the acid-base properties at pH < PZC and has a concentration of 1.2 × 10-3 mol/g FeS. At higher pH, the tricoordinated sulfur, which has a concentration of 1.2 × 10-3 mol/g FeS, determines surface charge changes. Total site density is 4 sites nm-2. The acid-base titration data are used to develop a surface complexation model for the surface chemistry of FeS. Copyright © 2005 Elsevier Ltd.
Keywords: mackinawite